Residential Care Transformed - Johnson, J. author. aut Link
XIX, 285 p.
Keywords: This book, now in paperback, revisits Peter Townsend's classic study of residential care for older people in Britain conducted in the late 1950s. It provides not only a fascinating account of residential care for older people over the last 50 years but is also an important contribution to the literature on research methods.